2011
DOI: 10.1007/s10529-011-0775-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of pH stability and activity of glycerol dehydratase from Klebsiella pneumoniae by rational design

Abstract: Glycerol dehydratase (GDHt) is a key and rate-limiting enzyme in the pathway of 1,3-propanediol (1,3-PD) synthesis. The improvement of GDHt's stability and enzymatic activity is desirable for the biosynthesis of 1,3-PD. The gldABC gene encoding GDHt of Klebsiella pneumoniae was cloned and expressed in Escherichia coli XL10-Gold, and the mutation sites of GDHt were obtained through prediction by PoPMuSiC program. Consequently, two mutants (KpG60 and KpG525) were developed by rational design through site-mutagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 22 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Only one study reported about its protein engineering using subunit gene swapping [ 84 ]. The thermal, pH stability, and V max of the GDHt were markedly improved by 2-5 times compared with the wild type by rational design [ 84 , 85 ]. PoPMuSiC is an effective computer-aided rational design program for site-mutation study of proteins or polypeptides [ 86 ].…”
Section: Glycerol Dehydratasementioning
confidence: 99%
“…Only one study reported about its protein engineering using subunit gene swapping [ 84 ]. The thermal, pH stability, and V max of the GDHt were markedly improved by 2-5 times compared with the wild type by rational design [ 84 , 85 ]. PoPMuSiC is an effective computer-aided rational design program for site-mutation study of proteins or polypeptides [ 86 ].…”
Section: Glycerol Dehydratasementioning
confidence: 99%
“…PoPMuSiC evaluates the stability changes resulting from all possible mutations and returns a report containing a list of the most stabilizing mutations or destabilizing mutations, or the mutations that do not affect stability [18]. This algorithm has been proved useful in the design of stabilized point mutations of tobacco etch virus protease [19], pyruvate formate lyase [20], feruloyl esterases [21], glycerol dehydratase [22], keratinase [23], alkaline ␣-amylase [24] and some other enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…With our stabilized Kp GDHt‐L scaffold in hand, we were able to design and implement a high‐throughput screen that was capable of assessing thousands of variants. We aimed to build on previous site‐directed mutagenesis approaches and explore the ability of CASTing to uncover synergistic combinations of point mutations in the active site. The catalytic mechanism of the B 12 ‐dependent dehydratases is complex, requiring coordination of the catalytic K + ion and exquisite control over the radical that is generated upon homolytic cleavage of the Co–C bond of adenosylcobalamin .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the only previous attempt to improve the activity of Kp GDHt by site‐directed mutagenesis was by computational design . The authors used the PopMuSiC algorithm to design single site mutations that were predicted to stabilize the structure of the enzyme.…”
Section: Introductionmentioning
confidence: 99%